Conceptualising the benefit framework of an enterprise content management system (ECMS) / Mohamad Rahimi Mohamad Rosman and Mohamad Rahimi Mohamad Rosman - Mohamad Rosman, Mohamad Rahimi; Abdul Aziz, Mohammad Azhan (Universiti Teknologi MARA Shah Alam, 2018)
Content management is an organisational effort of managing content, particularly in digital format. Although it has been over 25 years since content management was introduced, this field of study is still considered an emerging topic with unresolved issues-in particular, the subject of benefit achievement. Therefore, grounded on an extensive review of 135 articles, the purpose of this study is to investigate the benefits that organisations can gain through the proper use of an Enterprise Content Management System (ECMS). Subsequently, this paper identifies a list of ECMS benefits and proposes an ECMS benefit framework for further exploration into this field. Our result shows that although ECMS does bring benefits to organisations, these benefits are diverse; indicating that there are certain determinants or factors influencing the achievement of such benefits. Moreover, it is also found that in the context of the benefit framework of Shang and Seddon [10], three categories were found relevant to the field of content management: operational benefit, managerial benefit, and strategic benefit.